Genetic Differentiation of Ornamental and Fruit-Bearing Prunus laurocerasus Revealed by SSR and S-Locus Markers - Attila Hegedűs; Péter Honfi; Sezai Ercisli; Gulce Ilhan; Endre György Tóth; Júlia Halász (Horticulturae)
Cherry laurel (Prunus laurocerasus) is an understudied, highly polyploid (22×) species that is widely used as an ornamental shrub and as a fruit-bearing plant in Türkiye. We analyzed 43 accessions—33 ornamental cultivars and 10 fruit-bearing selections—by examining size variations in 10 simple sequence repeat (SSR) markers and the first intron region of the self-incompatibility ribonuclease (S-RNase) gene. A total of 498 alleles were detected across 11 loci, with the highest number of alleles observed at the S-locus. The SSR loci amplified between 4 (ASSR63) and 17 (BPPCT039) alleles per accession, with eight of the 11 primers generating more than 12 alleles per accession. Two markers, BPPCT040 and CPSCT021, uniquely distinguished all tested accessions. Of the alleles, only 178 (36%) were shared between the ornamental and fruit-bearing groups, reflecting significant genetic differentiation. A dendrogram and principal coordinate analysis revealed three distinct groups. Group 1 included most Hungarian and some European cultivars. Groups 2 (Western European cultivars) and 3 (Turkish selections) exhibited higher average allele numbers, suggesting greater genetic diversity in these groups. Our results indicate that cultivated cherry laurels originate from a broad genetic base and show clear genetic divergence between ornamental and fruit-bearing selections, likely due to differing long-term selection pressures. The observed genetic variability is consistent with the polyploid nature of the species and supports the presumed self-incompatible phenotype. This is the first study to report SSR fingerprints for ornamental cultivars and fruit-bearing selections, providing a potential tool for use in breeding programs.